Analysis of random data hopping in distributed multihop wireless networks - Venkataraman, H.; Muntean, G.-M. (TENCON 2008 - 2008 IEEE Region 10 Conference, 2008)
Spatial reuse TDMA (time division multiple access) in multihop ad hoc network is a subject of intense research interest for next generation wireless systems. In this paper, the selection of concurrent communication pairs, that utilize the same resources, is formulated as a non-linear mixed integer programming problem. However, it has been found that the solution to this non-linear programming problem is NP-hard. Recently, a random data hopping (RDH) technique applied over a time slot partitioned system has been proposed by the authors as a novel heuristic algorithm. This random data hopping scheme is further studied in this paper for different values of traffic loads, and its performance is evaluated under realistic propagation conditions. It has been found that the variation of the system throughput with the traffic load follows a concave function, and it reaches its peak when the traffic load is around 30%.